Synthesis of cobalt(II)-α-diimines complexes and their activity as mediators in organometallic mediated radical polymerization of vinyl acetate - Riga, Beatriz A. [UNESP]; Neves, Marina D. [UNESP]; Machado, Antonio E.H.; Araújo, Diesley M.S.; Souza, Jhonathan R.; Nascimento, Otaciro R.; Santana, Vinícius T.; Cavalheiro, Carla C.S.; Carvalho-Jr, Valdemiro P. [UNESP]; Goi, Beatriz E. [UNESP] (Elsevier, 2018)
This study describes the synthesis and characterization of three α-diimine-cobalt complexes of the type [CoCl2(R-DAB)] (R-DAB = R–N[dbnd]CH–CH[dbnd]N–R; R = Mes, Dipp and Dipp∗) and their application as mediators for the cobalt-mediated radical polymerization (CMRP) of vinyl acetate (VAc) using 2,2′-Azobis(2-methylpropionitrile) (AIBN) as initiator. The complexes were characterised by elemental analyses, FTIR, UV–Vis, electron paramagnetic resonance spectroscopy, cyclic voltammetry, and computational methods. The systematic variation of the reaction conditions, such as [initiator]/[Co] and [monomer]/[Co] molar ratios at 65 °C, affected the polymerization rates and the molecular weights, reaching a certain level of control. The VAc polymerization was initiated by AIBN in the presence of DMSO using the α-diimine-cobalt complexes as mediators with [DMSO]/[Co] = 1 at 65 °C. The control over the polymer produced was not improved after the addition of DMSO. Kinetics studies and computational investigations support a tailorable cobalt complex reactivity mainly altered by steric factors of the α-diimine ligands.
Keywords: CMRP; Radical polymerization; Vinyl acetate; α-Diimine-cobalt complexes